ACADEMIC STRESS IS ASSOCIATED WITH EMOTIONAL EATING BEHAVIOR AMONG ADOLESCENT - Nadia Ramadhani; Trias Mahmudiono (Media Gizi Indonesia, 2021)
Academic stress is one of the sources of stress factor among adolescent. Stress condition will trigger cortisol reaction process which associated with unhealthy eating behavior. Emotional eating is an eating behavior in response to stimulation of negative emotion. This study aims to analyze the association between academic stress with emotional eating behavior among adolescent at SMAN 6 Surabaya. This study used a cross sectional design. Samples were obtained using Cluster Random Sampling techniques with total sample of 133 people. Data were collected using the Educational Stress Scale for Adolescent (ESSA), Dutch Eating Behavior Questionnaire (DEBQ) and Food Frequency Questionnaire (FFQ). Kolmogorov-Smirnov was used to determine the normality of data obtained. Association between variables was analyzed using Spearman correlation. The results showed that 47,4% students experienced moderate academic stress and 51,1% of students experienced emotional eating. There was signifi cant association between academic stress with emotional eating behavior (p=0.003). Emotional eating behavior was positively correlated with consumption of fast food or canned food, sweet food or cakes, dairy products and sweet beverages.